L’ASCENSION SPECTACULAIRE DES MANŒUVRES DILATOIRES DANS LES PRATIQUES PRETORIENNES : UN VERITABLE ASPHYXIANT DU DROIT A LA CELERITE DU PROCES PENAL EN R.D. CONGO - Kausa, Kakule (IJRDO - Journal of Social Science and Humanities Research, 2025)
This article seeks to demonstrate that the dilatory maneuvers observed in judiciary practices lead to denials of justice and make the right to a speedy criminal trial in the D.R. Congo an illusion. The reflection aims to propose palliative measures and advocates for a jurisprudential revolution accompanied by legislative reform in procedural law. It also calls for stringent disciplinary actions against lawyers and legal defenders engaged in dilatory tactics.